Comparing the SureSight autorefractor and the plusoptiX photoscreener for pediatric vision screening. (June 2014) - Silbert, David; Matta, Noelle; Tian, Jing; Singman, Eric
Abstract Purpose: Both the plusoptiX photoscreener photoscreener and the SureSight autorefractor can be used to objectively screen for amblyogenic risk factors in children. We compare the plusoptiX and the SureSight to a pediatric ophthalmology examination on a single cohort of children. Methods: We performed a retrospective medical records review of 90 children. Each patient was screened with both the PlusoptiX A09 and SureSight devices on the same day as part of a comprehensive pediatric ophthalmic examination. The ages of the patients ranged from <1 to 17 years. All patients had a cycloplegic refraction on the day of their exam, or within the previous 6 months. Results: Of the children reviewed, 71% had amblyopia risk factors. The plusoptiX demonstrated a sensitivity of 98% and a specificity of 88%. The SureSight demonstrated a sensitivity of 95% and a specificity of 65% utilizing the manufacturer's criteria. Conclusion: The SureSight and plusoptiX were both found to be reliable objective vision screening devices, though the plusoptiX did have a higher sensitivity and specificity than the SureSight using the manufacturer's referral criteria. Using the Vision In Preschoolers Study (VIPS) referral criteria, the specificity of the SureSight improved but the sensitivity was reduced.